Jammer against eavesdropper in half-duplex energy harvesting cooperative relaying networks: secrecy outage probability analysis - Phu Tran Tin; Duy-Hung Ha; Minh Tran; Tran Thanh Trang (Institute of Advanced Engineering and Science, 2020)
In this paper, we have investigated the Half-Duplex (HD) Energy Harvesting (EH) Cooperative Relaying Networks with one source node, one destination node, one intermediate relay and in the presence of the Jammer Against Eavesdropper. We have analyzed the system performance in terms of the integral form expression of secrecy outage probability. In addition, we have investigated the effect of source rate, time switching factor, energy coefficient, and the ratio Ps/N0 on the system performance. Finally, all the mathematical, analytical expressions are verified by Monte Carlo simulation, and the analytical results match well with the simulation ones to convince the correctness of the analytical expression.